Peran Panti Asuhan Miftahul Jannah Dalam Pemberdayaan Keagamaan Anak Yatim di Kecamatan Kotapinang - Dinda Salsabila Harahap; Salamuddin Salamuddin (Assyfa Journal of Islamic Studies, 2026)
The purpose of this study was to determine the involvement of the Miftahul Jannah Orphanage in empowering orphans in Kotapinang, the types of empowerment programs implemented, and the factors that facilitate or hinder their implementation. This study used a descriptive research design and qualitative methodology. Data collection techniques included note-taking, interviews, and observations. The village head, foster children, caregivers, orphanage managers, and local community members served as informants in this study. Data reduction, data presentation, and drawing conclusions using source triangulation and data validation procedures were the methods used for data analysis. The research findings indicate that the Miftahul Jannah Orphanage plays a significant role in empowering orphans through character development, religious activities, educational supervision, and the development of skills and independence of foster children. In addition, the existence of the orphanage benefits the surrounding environment by fostering a solemn and peaceful atmosphere, increasing social awareness, and encouraging collaboration. Donors, the local government, and the community all provide support for the implementation of orphan empowerment. Meanwhile, there are several obstacles that must be overcome, such as the scarcity of dormitories and the increasing costs of housing and education for foster children. The Miftahul Jannah Orphanage has successfully fulfilled its role as a social institution in empowering orphans in Kotapinang, according to the study's findings. Therefore, the government and community must continue to support this empowerment initiative so it can grow and be more beneficial to the orphans.